Domain engineering approach of software requirements analysis - Chebanyuk, O.V.; Palahin, O.V.; Markov, K.K. (Проблеми програмування, 2020)
Requirement analysis is one of the important processes in software development lifecycle management. In Agile approach requirements software models are the basic of generating other software development artifacts. Improving requirements approaches and techniques allows avoiding mistakes in other software development artifacts. Domain engineering fundamentals is the basic for “template oriented” approaches of software development artifacts designing. Reusing domain models and knowledge allows adding details in vertical “model to model” transformation operations, refine generated software development artifacts, organize systematic software reuse and perform many other activities. Paper proposes an approach of requirement analysis based on UML Use Case diagrams transformations into communication ones and the next refinements of them by means of information from domain models. The advantages of the proposed approach is the next: proposed transformation method involves ”many to many” transformation in order to save the semantic of initial model. Domain knowledge are used to complete communication diagram by means of adding details after transformation to them. In order to perform Use case to communication transformation graph representation of software models is chosen.